2018
DOI: 10.1167/iovs.17-23546
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance and Repeatability of a Novel Game-Based Visual Field Test for Children

Abstract: The Caspar's Castle system of assessing visual fields using novel game-based strategies demonstrates encouraging levels of sensitivity, specificity, and reliability. It could help address current difficulties in perimetry in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We believe that eye tracking applications might prove useful when testing VFs in children in the future. 32–34 Furthermore, predicting VFDs using OCT seems to be possible in children with a developmental age of 3–6 years. 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that eye tracking applications might prove useful when testing VFs in children in the future. 32–34 Furthermore, predicting VFDs using OCT seems to be possible in children with a developmental age of 3–6 years. 35 …”
Section: Discussionmentioning
confidence: 99%
“…6 We believe that eye tracking applications might prove useful when testing VFs in children in the future. [32][33][34] Furthermore, predicting VFDs using OCT seems to be possible in children with a developmental age of 3-6 years. 35 In our centre the Octopus perimeter is not available and the HFA is sparsely used in children due to the extensive and positive experience of staff in testing children with or without NI using the Peritest.…”
Section: Perimetry Tests Usedmentioning
confidence: 99%
“…Rossana Terracciano, Alice Mascolo, Laura Venturo, Federica Guidi, Mariangela Vaira, Chiara M. Eandi and Danilo Demarchi, Senior Member, IEEE V with restrictive neck conditions [30], and the possibility to expand the option of remote testing. In addition, diagnostic utility of VR has been demonstrated to address current challenges associated with inattention and poor compliance for the detection of visual field defects in children [31]. Tsapakis et al [32], [33] presented a visual field examination method using virtual reality glasses which implements static perimetry and evaluated the reliability of the method in glaucoma patients by comparing the results with those of a standard perimeter obtaining promising correlation results.…”
Section: Kinetic Perimetry On Virtual Reality Headsetmentioning
confidence: 99%
“…Optimal approaches to Members of the OPTIC Study Group are listed below assessing the VF are less well defined. To address this, we have previously investigated the relative strengths of static, kinetic, and combined static and kinetic techniques in children with glaucoma [9], adding information about the use of optimised static perimetry algorithms such as the Humphrey SITA 24-2 FAST (Swedish Interactive Thresholding Algorithm, Carl Zeiss Meditec AG, Jena, Germany) and Octopus G-TOP (Tendency-Oriented Perimetry, Haag-Streit Holding AG, Koeniz, Switzerland) to existing data on rarebit [10], supra-threshold [11] and game-based techniques [12]. Our research also demonstrated the utility of combined static/kinetic perimetry for monitoring VF defects in children with severe glaucoma [9].…”
Section: Introductionmentioning
confidence: 99%